Students' Interest in Learning English and Reading Understanding Ability Using Story Texts - Rachman, Dzul (LPPM Universitas Mercu Buana Yogyakarta, 2018)
This research analyzed the correlation of students’ interest and reading comprehension. The goals of the research are to realize the score of students’ interest in studying English, the score of reading comprehension, and to prove the giant correlation of students’ interest in studying English and reading comprehension capability. This research used quantitative research. The researcher implemented questionnaire to locate the score of students’ interest, and the researcher implemented a test to locate the score of studying comprehension of the 10th-grade students of SMAN 13 Samarinda. The result of this research showed that score of students’ interest of the 10th-grade students of SMAN 13 Samarinda is good. it could be seen from the end result of students’ interest score is 76.33. It showed that the students have interest in reading due to the fact they parents ask for reading English regularly, having a hobby in listening lyric songs and English movies increase vocabularies and that they take notes and recollect English difficult words then find out the that means. on this research also confirmed that score of reading comprehension the respondents is good. It additionally proved that there has been a correlation of students’ interest in getting to know English and their reading comprehension ability the use of narrative texts.